2010
DOI: 10.1002/jsfa.3936
|View full text |Cite
|
Sign up to set email alerts
|

Consumers' purchase intention of organic food in China

Abstract: Based on the results, the following measures are recommended: reduce the cost of organic food through multiple channels to cut down the market price; establish and perfect the supervision system of organic food; and promote organic food through various channels.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

24
266
4
6

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 280 publications
(300 citation statements)
references
References 47 publications
(38 reference statements)
24
266
4
6
Order By: Relevance
“…From a marketing perspective, it is critical to understand how Chinese consumers view innovations in the agro-food system and who adopts them. The number of studies conducted on Chinese consumers and organic food is growing (Roberts and Rundle-Thiele, 2007;Yin, Wu, Du and Chen, 2010;Sirieux et al, 2011;Bing et al, 2011;Lobo and Chen, 2012;Marchesini et al, 2012;Thøgersen and Zhou, 2012;Thøgersen et al, 2015;Yip and Janssen, 2015). The literature shows that gender, age, family size and average household income per year are the main socio-economic factors influencing willingness to pay for green food (Xia and Zeng, 2007;Xia and Zeng, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…From a marketing perspective, it is critical to understand how Chinese consumers view innovations in the agro-food system and who adopts them. The number of studies conducted on Chinese consumers and organic food is growing (Roberts and Rundle-Thiele, 2007;Yin, Wu, Du and Chen, 2010;Sirieux et al, 2011;Bing et al, 2011;Lobo and Chen, 2012;Marchesini et al, 2012;Thøgersen and Zhou, 2012;Thøgersen et al, 2015;Yip and Janssen, 2015). The literature shows that gender, age, family size and average household income per year are the main socio-economic factors influencing willingness to pay for green food (Xia and Zeng, 2007;Xia and Zeng, 2008).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Additionally, acceptability is an important food choice motivation when the consumer makes decisions regarding everyday food shopping (Chen, 2007). Organic food is a more sustainable alternative than conventional food (Thøgersen, 2010) because organic food is perceived as much more healthy, natural, nutritious, and sustainable than conventional foods (Hughner et al, 2007;Yin et al, 2010). Hence, it is believed that the consumer's attitude to organic foods purchase is positively related to the attitude to organic foods.…”
Section: A Marketing MIXmentioning
confidence: 99%
“…So, if the consumer perceives that organic food has value (e.g. egocentric values, such as health or pleasure) (Zanoli & Naspetti, 2002) and benefits, they might be willing to pay a higher price (Tse, 2001;Shaharudin et al, 2010). Organic food purchases are largely connected to consumers' environmental concerns, concerns about food quality, and/or safety.…”
Section: A Marketing MIXmentioning
confidence: 99%
“…The government of China has promoted an industrial agriculture characterized by heavy reliance on synthetic chemicals to protect crops against weeds, pests and diseases, thus leading to improved productivity. Nevertheless, the lack of sufficient training of farmers has resulted in the inadequate use of pesticides; that is, the recommended application levels and application frequency are not always followed, nor is the pre harvest interval strictly observed [37].…”
Section: Introductionmentioning
confidence: 99%
“…In a recent survey, half of the participants did not know how to distinguish organic food from green food [42]. Similarly, [37] found that consumers' knowledge on organic food is rather limited in China when compared to developed countries still; knowledge about organic food may differ between cities and food categories. A study in Chengdu showed that 91% of the participants knew about organic food in general while another study conducted in Shanghai and Nanjing showed that only 38% of the participants knew about organic pork [20].…”
Section: Introductionmentioning
confidence: 99%